Relato de avaliação da vida acadêmica - Silva, Majorie Valério Lopes da (Universidade Federal de São Carlos, 2023)
The Medical Course at the Federal University of São Carlos offers a different curricular proposal, which includes active methodologies of teaching and learning. There are few studies evaluating the impacts of adopting these educational resources on the experiences of the students. In order to discuss the theme, this work dialogues with the Academic Life Assessment Scale. The ALAS is a scale composed of affirmations divided into five self-referred factors for academic life. On the matters of commitment to the course, there were few uncertainties about the option and the affinities with the graduation course. Previous repertory and personal abilities were advantageous in the processes of getting a degree. Some considerations about teacher training within the university environment could guarantee a better development of the activies for the students. Academic, social and cultural extracurricular activities are enriching experiences in academic life, specially concerning a public university. There were no problems with the conditions for studying, however some vulnerabilities for the future are appearing.
Academic life evaluation report
Keywords: Educação em medicina; Aprendizagem baseada em problemas; Escala de avaliação da vida acadêmica; Estudante de medicina; Student medical; Medicine education; Problem-based learning; Academic life assessment scale; CIENCIAS DA SAUDE::MEDICINA